نظراتٌ في بلاغة النَّص المناسبة بين خواتيم سورة يونس ومفتتح سورة هود في ضوء نظرية النظم : Some Gazes of Quran Inimitability: The Harmonised between The Epilogues of Surat Yunus and The Beginnings of Surat Hud According to The Theory of Arabic Syntax An-Nazm - Mohamed Shehata (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2022)
This study aims to use a theoretical framework, which is mixed between modern applied linguistics and the theory of Arabic syntax "an-nazm" of Aljurjani while analyzing some topic of inimitability "I'jaz". That theoretical framework uses the grammatical links while looking in modern items like text coherence, reference, anaphora, and referral. This mixture enables us to connect between applied linguistic items and Arabic rhetorics. At the same time, it enables us to look for the beauty of linguistic structure, and to en-wide the items delivered from the old theory of syntax "an-nazm" while using it in analyzing different text, especially Quran, to figure out its Inimitability which we can find, here, at the harmonised between the epilogues of Surat Yunus and the beginnings of Surat Hud.